2016
DOI: 10.1021/acs.jpcb.6b01793
|View full text |Cite
|
Sign up to set email alerts
|

Onset of the Electronic Absorption Spectra of Isolated and π-Stacked Oligomers of 5,6-Dihydroxyindole: An Ab Initio Study of the Building Blocks of Eumelanin

Abstract: Eumelanin is a naturally occurring skin pigment which is responsible for developing a suntan. The complex structure of eumelanin consists of π-stacked oligomers of various indole derivatives, such as the monomeric building block 5,6-dihydroxyindole (DHI). In this work, we present an ab initio wave-function study of the absorption behavior of DHI oligomers and of doubly and triply π-stacked species of these oligomers. We have simulated the onset of the electronic absorption spectra by employing the MP2 and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 91 publications
7
37
0
Order By: Relevance
“…, the spectra are characterized by smooth, structureless, wide band behaviour, with exponential absorption at lower wavelenghts and optical density with a steep increase in the visible range but without a clearcut absorption edge. Such spectral behaviour is consistent with the semiconductor character of the material; in fact the monotonic exponential broad band absorption coefficient results from the ‘chemical disorder’ whereby several chromophores, with their distinct and broadened inhomogeneous spectral features, overlap each other . Therefore the optical measurements of the eumelanin films suggest a better organization for the indolic/phenolic components without affecting their distribution and show an increased degree of π ‐stacked oligomers .…”
Section: Resultssupporting
confidence: 70%
“…, the spectra are characterized by smooth, structureless, wide band behaviour, with exponential absorption at lower wavelenghts and optical density with a steep increase in the visible range but without a clearcut absorption edge. Such spectral behaviour is consistent with the semiconductor character of the material; in fact the monotonic exponential broad band absorption coefficient results from the ‘chemical disorder’ whereby several chromophores, with their distinct and broadened inhomogeneous spectral features, overlap each other . Therefore the optical measurements of the eumelanin films suggest a better organization for the indolic/phenolic components without affecting their distribution and show an increased degree of π ‐stacked oligomers .…”
Section: Resultssupporting
confidence: 70%
“…14 shows selected chemical filter molecules currently used in commercial sunscreens. 185 These broadly partition into seven classes,…”
Section: Molecular Constituents In Commercial Sunscreensmentioning
confidence: 99%
“…Tuna et al indicated that the -stacking of DHI and its oligomers substantially red-shifts the onset of the absorption spectrum. 98 Equilibrium structures of different intermediates such as dimers, 97,99,100 tetramers, 44,101 hexamers 89 and other oligomers 91 have been examined by evaluating their energy. Supramolecular interactions 96 and aggregated structures 22,90 of melanin-like compounds have also been investigated by using simulation methods.…”
Section: The Methodology For Characterization Of Melanin-like Materialsmentioning
confidence: 99%
“…In addition, there are a growing number of studies which have reported investigations of the structures and properties of melanin‐like materials by using theoretical calculations . These computations and other experimental research complement each other in deepening our understanding of synthetic melanins.…”
Section: The Modulation Of Melanin‐like Materialsmentioning
confidence: 99%
See 1 more Smart Citation